Effect of ash content on the combustion process of simulated MSW in the fixed bed. (February 2016) - Sun, Rui; Ismail, Tamer M.; Ren, Xiaohan; Abd El-Salam, M.
Graphical abstract: Highlights: The effect of the ash content on the burning process is investigated. 2D unsteady mathematical model was built to simulate the combustion process. Temperature, gas species and characteristics NO release are measured and simulated. The simulation results in the bed are accordant with the experimental results. MSW with low ash content are preferable. Abstract: This paper experimentally and numerically investigates the effects of ash content on the combustion process of simulated Municipal Solid Waste (MSW). A fixed-bed experimental reactor was utilized to reveal the combustion characteristics. Temperature distributions, ignition front velocity, and the characteristics of gas species' release were measured and simulated during the combustion process. In the present work, the two-dimensional unsteady mathematical heterogeneous model was developed to simulate the combustion process in the bed, including the process rate model as well as NOx production model. The simulation results in the bed are accordant with the experimental results. The results show that as ash content increases, the lower burning rate of fuel results in char particles leaving the grate without being fully burned, causing a loss of combustible material in the MSW in a fixed bed and therefore reducing the combustion efficiency and increasing the burning time of the MSW.